Die Rechnung der Momente und der Komulanten des Zahles de Wiederstellungen im Falle des diskreten Wiederstellungprozesses - Liutikas, V. (Lithuanian Mathematical Journal, 1966)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. Лютикас. Вычисление моментов и семиинвариантов числа восстановлений в случае дискретного процесса восстановления V. Liutikas. Atstatymų skaičiaus momentų ir semiinvariantų skaičiavimas diskretinio atstatymo proceso atveju